Mewujudkan Kreativitas Santri melalui Pelatihan Konten Digital di Pesantren Nurul Qur'an Kedungwuni Pekalongan - Anam, Khoirul; Arfani, Zidni; Hartono, Prasetyo Rejo; Saputra, Yusuf Agung; Adinugraha, Hendri Hermawan; Syafi’i, Muhammad Aris (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Many people think that Islamic boarding schools only focus on religious knowledge, even though now they also emphasize general knowledge, including technology and information skills. The training at the Nurul Qur'an Islamic Boarding School aims to provide skills in digital media content production to students in Podo Village, Kedungwuni District, Pekalongan. Using a community-based research (CBR) approach, training involves collaboration between the community and higher education institutions with a focus on real action. Training materials include photography, videography, and design using the Canva application. As a result, participants immediately put into practice the material provided, increasing their understanding of creating interesting and effective digital content. Suggestions for ongoing training can expand knowledge and the application of acquired skills.